Separation of lactic acid and by-products obtained by catalytic conversion of glycerol using high-performance liquid chromatography - Cruz, Andreza de Faria Alves; Dias, Gabriella Pinho; Bittencourt, Flávia de Rezende; Aranda, Donato Alexandre Gomes (Eclética Química, 2022)
Lactic acid is an attractive raw material in synthesizing many products. A new method for quantifying glycerol, lactic acid, and the by-products (pyruvaldehyde) obtained in this reaction was developed using high-performance liquid chromatography (HPLC) with a refractive index detector (HPLC-RI) in a column (300 × 7.7 mm, 8 µm) using H2SO4 0.001 M + 10% ACN (organic modifier) as mobile phase (0.6 mL min–1). This method indicated outstanding linearity for glycerol and lactic acid concentration from 0.6 to 6.6 g L–1 (coefficient of determination (R²) = 0.9912 and 0.9961, respectively) and accuracy between 98.33 and 100.00%. From this, it was possible to conclude that the method is applicable and concise for separating the primordial products in this reaction.